ANALYSIS OF SUPPORTING FACTORS AND CHALLENGES IN IMPLEMENTING KAIZEN CULTURE IN SMALL AND MEDIUM ENTERPRISES - Aus, Fari (Journal of Finance, Economics and Business, 2024)
The Kaizen culture, which focuses on continuous improvement, has been widely implemented in the company big, but its implementation in Small and Medium Enterprises (SMEs) is still facing various challenges. This study aims to identify factor supporters and challenges key in the implementation of Kaizen in the SME environment. Using a qualitative approach, data was collected through interview in-depth with SME owners and managers as well analyzed use thematic analysis technique. The results of the study show that although Kaizen can improve productivity, efficiency and satisfaction customers, SMEs often experience constraints related to limited resources, competence managerial, and support external. This finding confirms importance Kaizen adaptation in the context of SMEs and its relevance for the development of competitiveness term length. Implications This research practice includes recommendation for stakeholders’ interest in providing training and support special for SMEs who want to implementing Kaizen culture.